Pleural fluid soluble triggering receptor expressed on myeloid cells-1 as a marker of bacterial infection: a meta-analysis - Jiang Hong-Ni; Zhu Ying-Gang; Tao Li-Li; Summah Hanssa; Qu Jie-Ming (BMC Infectious Diseases, 2011)
Abstract Background Pleural infection is a common clinical problem. Its successful treatment depends on rapid diagnosis and early initiation of antibiotics. The measurement of soluble triggering receptor expressed in myeloid cells-1 (sTREM-1) level in pleural effusions has proven to be a valuable diagnostic tool for differentiating bacterial effusions from effusions of other etiologies. Herein, we performed a meta-analysis to assess the accuracy of pleural fluid sTREM-1 in the diagnosis of bacterial infection. Methods We searched Web of Knowledge and Medline from 1990 through March 2011 for studies reporting diagnostic accuracy data regarding the use of sTREM-1 in the diagnosis of bacterial pleural effusions. Pooled sensitivity and specificity and summary measures of accuracy and Q* were calculated. Results Overall, the sensitivity of sTREM-1was 78% (95% CI: 72%-83%); the specificity was 84% (95% CI: 80%-87%); the positive likelihood ratio was 6.0 (95% CI: 3.3-10.7); and the negative likelihood ratio was 0.22 (95% CI: 0.12-0.40). The area under the SROC curve for sTREM-1 was 0.92. Statistical heterogeneity and inconsistency were found for sensitivity (p = 0.015, χ2 = 15.73, I2 = 61.9%), specificity (p = 0.000, χ2 = 29.90, I2 = 79.9%), positive likelihood ratio (p = 0.000, χ2 = 33.09, I2 = 81.9%), negative likelihood ratio (p = 0.008, χ2 = 17.25, I2 = 65.2%), and diagnostic odds ratio (p = 0.000, χ2 = 28.49, I2 = 78.9%). A meta-regression analysis performed showed that the Quality Assessment of Diagnostic Accuracy Studies score (p = 0.3245; RDOR, 4.34; 95% CI, 0.11 to 164.01), the Standards for Reporting of Diagnostic Accuracy score (p = 0.3331; RDOR, 1.70; 95% CI, 0.44 to 6.52), lack of blinding (p = 0.7439; RDOR, 0.60; 95% CI, 0.01 to 33.80), and whether the studies were prospective or retrospective studies (p = 0.2068; RDOR, 7.44; 95% CI, 0.18 to 301.17) did not affect the test accuracy. A funnel plot for publication bias suggested a remarkable trend of publication bias. Conclusions Our findings suggest that sTREM-1 has a good diagnostic accuracy and may provide a useful adjunctive tool for the diagnosis of bacterial pleural effusions. However, further studies are needed in order to identify any differences in the diagnostic performance of sTREM-1 of parapneumonic effusions and empyemas.